Scarcity Marketing and Impulse Buying in Live Commerce: The Mediating Role of Emotional Arousal and Social Influence - Dwi Erlin Effendi (Journal of Marketing Breakthroughs, 2026)
Objective: This study aims to analyze the influence of scarcity marketing and social influence on impulse buying among live commerce consumers in Indonesia, while examining the mediating role of emotional arousal within the Stimulus-Organism-Response (S-O-R) framework. Research Design & Methods: Utilizing an explanatory quantitative research design, data were collected through an online Likert-scale questionnaire distributed via purposive sampling to 207 active live commerce users (e.g., Shopee Live and TikTok Shop) across Indonesia. The structural equation model was analyzed using Partial Least Squares (PLS-SEM). Findings: The empirical results indicate that both scarcity marketing and social influence have a positive and significant effect on emotional arousal and impulse buying. Interestingly, social influence exerts a stronger effect on impulse buying and emotional arousal than scarcity marketing in the live commerce environment. Furthermore, mediation analysis confirmed that emotional arousal significantly bridges the impact of both external marketing stimuli and social interactions on impulsive purchasing behavior. Contribution: This research extends the S-O-R framework by demonstrating how interactive real-time digital cues function as powerful emotional triggers. It enriches digital consumer behavior literature by shifting the focus from individualistic e-commerce to highly collaborative and socially-driven live streaming ecosystems in emerging markets. Novelty: The novelty of this study lies in the shift in the focus of live commerce research from a purely transactional perspective to in-depth psychological mechanisms. By integrating Cialdini’s principles of scarcity and social proof into the S-O-R framework, this study empirically demonstrates that Social Influence (β = 0.480) has a stronger effect than Scarcity Marketing (β = 0.392) in triggering emotional arousal and spontaneous purchases in emerging markets such as Indonesia.